Predictors for COVID‐19‐related new‐onset maladaptive behaviours in children presenting to a paediatric emergency department. (27th May 2021) - Heyming, Theodore W; Fortier, Michelle A; Martin, Sarah R; Lara, Bryan; Bacon, Kellie; Kain, Zeev N
Abstract : Background and Objective: The goal of the present study was to determine the incidence of new onset maladaptive behaviours in paediatric emergency department (PED) patients during the COVID‐19 pandemic and to examine whether child and parent anxiety and parental health status were predictors for the new‐onset of maladaptive behaviours. Methods: Participants included child–parent dyads seen in a PED following the state's issuance of mandatory stay‐at‐home orders on 19 March 2020. A total of 351 children age 0–25 years and 335 parents enrolled in the study. Parents provided baseline demographic data and completed standardised surveys that assessed aspects of parental and child anxiety and parental health, as well as child new‐onset maladaptive behaviours. Children ≥8 years of age completed surveys that assessed child anxiety. Findings: Parents reported the new onset of maladaptive behaviours in children during the pandemic with frequencies up to 43%. Bivariate analysis identified predictors such as child anxiety ( t (96) = −2.04, P = 0.044) as well as parental variables such as state anxiety ( t (190) = −4.91, P < 0.001) and parental sensitivity to anxiety ( t (243) = −3.19, P = 0.002). A logistic regression model identified parent mental health and COVID‐19 anxiety as predictors of new onset maladaptive behaviours in children ( X 2 (6) = 42.514, P < 0.001). Specifically, every unit change in parental anxiety of COVID‐19 was associated with a unit increase in maladaptive behaviours in children. Conclusions: We identified distinct parent and child‐related factors that predicted new onset child maladaptive behaviours during the COVID‐19 pandemic. The identification of such predictors may help clinicians to prevent maladaptive responses to the pandemic quarantine.